2019
DOI: 10.3126/ojn.v9i2.28416
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Orthodontic Treatment Duration Among Extraction Versus Non Extraction Therapies

Abstract: Introduction: Orthodontic treatment is usually perceived as a lengthy treatment as average treatment time usually last more than a year and may go up to even five years. So, in orthodontic practice the optimum treatment result with minimal treatment time should be the goal of clinicians. Treatment duration varies based on different clinico-environmental factors. Materials & Method: Total 200 cases were randomly selected from the archives of debonded treatment records from the department of orthodonti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Additionally, a reliable idea of the treatment duration helps the orthodontist to better plan the overall treatment and the sequence of appointments (Fink and Smith, 1992;Mavreas and Athanasiou, 2008) [1,2]. Earlier studies reported that orthodontic treatment employing fixed appliances typically lasts 14 to 33 months (Kafle et al, 2019;Tsichlaki et al, 2016) [3,4] with a mean of around 22 to 24 months, depending on the discrepancy being treated (Aljehani and Baeshen, 2018;Simister, 2007) [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, a reliable idea of the treatment duration helps the orthodontist to better plan the overall treatment and the sequence of appointments (Fink and Smith, 1992;Mavreas and Athanasiou, 2008) [1,2]. Earlier studies reported that orthodontic treatment employing fixed appliances typically lasts 14 to 33 months (Kafle et al, 2019;Tsichlaki et al, 2016) [3,4] with a mean of around 22 to 24 months, depending on the discrepancy being treated (Aljehani and Baeshen, 2018;Simister, 2007) [5].…”
Section: Introductionmentioning
confidence: 99%
“…They range from general malocclusion, anatomic and biologic factors (such as bone morphology, patient age, and disease), the type of treatment (extraction versus nonextraction), to the planned treatment technique (Bhikoo et al, 2018) [6]. A further aspect might be patient cooperation, which is closely related to socio-economic factors and education (Kafle et al, 2019;Mavreas and Athanasiou, 2008;Tsichlaki et al, 2016) [2][3][4].…”
Section: Introductionmentioning
confidence: 99%